BL Kontribusi Affective Image Terhadap Peningkatan Revisit Intention Wisatawan Candi Cangkuang - Putri Saniah Nur Fadhillah; Yadi Ernawadi (UNIVED Press, 2023)
The purpose of this study was to examine the effect of destination image on revisit intention mediated by tourist satisfaction at Cangkuang Temple in Garut Regency. To achieve this goal using a survey method with questionnaires and respondents as many as 100 people with a minimum age of 17 years who have experience visiting tourist destinations that are the object of research. The data collection technique used is cross-sectional or one shot study. The data analysis technique used is multiple linear regression using SPSS version 25 and using the Sobel test. Of the ten proposed research hypotheses, there are five hypotheses that successfully reject H0. The findings of this study indicate that affective image have a positive effect on revisit intention through tourist satisfaction. Meanwhile, the use of other concepts to directly influence revisit intention can be proposed by future researchers. The results of this study are also useful for the management of the object being assessed and the similar tourism industry regarding the design of strategies that are relevant to improving the quality of these attributes.